Influence of growth regulators on callus induction and plant regeneration from anthers of Tagetes spp. - KUMAR, K RAVINDRA; SINGH, KANWAR PAL; JAIN, P K; RAJU, D V S; KUMAR, PRABHAT; BHATIA, REETA; PANWAR, SAPNA (The Indian Journal of Agricultural Sciences, 2024)
Marigold (Tagetes spp.) belongs to family Asteraceae, native to Mexico, is one of the most important flower crop grown commercially in different parts of India. The application of haploid techniques as anther culture can considerably accelerate marigold breeding programmes by providing homozygous doubled haploid (DH) lines for F1 hybrid seed production. Therefore, the objective of the present investigation was to study the effect of growth regulators for in vitro regeneration in both African marigold and French marigold genotypes viz., Pusa Basanti Gainda and Pusa Arpita, respectively for haploid induction. Among the different treatments tested for callus induction, anthers cultured on MS medium supplemented with 1.0 mg/l BAP + 1.0 mg/l 2,4-D + 45 g/l sucrose significantly induced highest (38.74%) callus in the shortest period of time (16 days). Among two genotypes tested, embryogenic callus induction (27.70%) was significantly higher in Pusa Arpita over Pusa Basanti Gainda (23.37%). Among the different regeneration treatments, the highest adventitious shoot bud induction (13.32%), maximum (1.09) number of buds/callus in shortest duration (19.47 days) was observed in anther derived callus cultured on MS medium supplemented with 2.0 mg/l BAP + 0.5mg/l NAA + 30 g/l sucrose. Among two genotypes evaluated for shoot bud induction, maximum (3.81%) regeneration was recorded in Pusa Arpita over Pusa Basanti Gainda (2.90%). In French genotype, the whole regeneration process was completed in 30 days whereas in African genotype it took nearly 40 days. This rapid regeneration system from anthers is highly useful in inducing haploids and di-haploids in African and French marigold lines, respectively.